The Effect of Inventory Management on Company Value (Empirical Study on Food and Beverage Sub-Sector Companies Listed on the Indonesia Effek Exchange in 2020-2023) - Devi Fuspanita; Hakiman Thamrin (Indonesian Journal of Business Analytics, 2024)
The purpose of this study is to test and analyze the influence of "Inventory Management" on Company Value, which is calculated using PBV. Inventory management is calculated using RMC, WIPC, FGC, INVTC. The research was conducted on F&B companies listed on the Indonesia Effek Exchange (IDX) with the period 2020-2023 using quarterly data. The method used by the Data Regression Panel. The results of the study showed that Inventory Management had an effect on PBV, and the RCM variable had an effect on PBV. Meanwhile, the variables of WIPC, FGC, INVTC had no effect on PBV.